Hsp70 regulates CD24 expression and promotes metastasis and invasion of lung cancer via the MAPK/ERK signaling pathway - Liu, Xin; Yu, Xinjing; Hu, Qun; Zhang, Ning; Zhang, Shuyu; Liu, Yang; Jia, Jiaqi; Qiao, Xiaojuan (Frontiers in Oncology, 2025)
PurposeTo investigate the effects and mechanisms of Hsp70-mediated regulation of CD24 expression on the invasion and metastasis of lung cancer.MethodsProtein-protein interactions between Hsp70 and CD24 were analyzed by co-immunoprecipitation and immunofluorescence. Lentiviral-mediated Hsp70 knockdown and CD24 overexpression were validated using RT-qPCR and Western blotting. Functional consequences were assessed through CCK-8 proliferation assays, colony formation, wound healing, Transwell migration/invasion, and angiogenesis assays. In vivo metastatic potential was evaluated using a tail vein injection model in nude mice.ResultsHsp70 and CD24 demonstrated interaction through co-precipitation. Knockdown of Hsp70 significantly attenuated CD24 expression (p<0.01), whereas CD24 overexpression did not alter Hsp70 levels. Phenotypically, Hsp70 suppression impaired cellular proliferation, migration, invasion and angiogenic capacity, while CD24 overexpression potentiated these oncogenic properties. Both manipulations modulated ERK1/2, MEK, Raf and Ras phosphorylation status.ConclusionHsp70 upregulates CD24 expression and activates downstream MAPK/ERK signaling, thereby enhancing the metastatic and invasive capacity of lung cancer.